Effects of resistance training on serum 25(OH) D concentrations in young men: a randomized controlled trial - Xiaomin Sun; Xiao-Kai Ma; Lin Zhang; Zhen-Bo Cao (Nutrition & Metabolism, 2020)
Abstract Background Previous studies indicated that serum 25-hydroxyvitamin D [25(OH)D] concentrations are positively associated with physical activity levels independent of sun exposure. However, the effect of resistance training on serum 25(OH) D concentrations remains unclear. Thus, this study aimed to examine the effect of chronic resistance training on serum 25(OH) D concentrations and determine whether 25(OH) D concentration variations are influenced by body composition changes. Methods Eighteen young men aged 19–39 years were randomly divided into a 12-week resistance training group (RT, n = 9) and non-exercise control group (CON, n = 9). The trial was undertaken in Shanghai University of Sport in Shanghai, China. Randomization and allocation to trial group were carried out by a central computer system. Serum 25(OH) D and intact parathyroid hormone concentrations were measured using commercially available enzyme-linked immunosorbent assay kits. Body composition was measured by dual-energy X-ray absorptiometry. Results The average serum 25(OH) D concentrations were 26.6 nmol/L at baseline. After the 12-week intervention program, serum 25(OH) D concentrations significantly increased in both groups. Serum 25(OH) D concentrations at midpoint (6-week) increased significantly only in the CON group (P < 0.01). From training midpoint to endpoint, a significantly greater increase in serum 25(OH) D concentrations was noted in the RT group (P-interaction = 0.043); 25(OH) D concentration changes (end-pre) were negatively related to fat-free mass (mid-pre) (r = − 0.565, P = 0.015) and muscle mass (mid-pre) (r = − 0.554, P = 0.017). Conclusions There were no beneficial effects of the 12-week resistance training on serum 25(OH) D concentration in vitamin D deficient young men, and an indication that seasonal increase in serum 25(OH) D concentrations during the early phase of resistance training was transiently inhibited, which may partly be attributed to resistance training-induced muscle mass gain. Trial registration Chinese Clinical Trial Registry, ChiCTR2000030876. Registered 16 March 2020 - Retrospectively registered, http://www.chictr.org.cn/showproj.aspx?proj=50504 .